Analisis Marjin Harga, Keuntungan, dan Share Keuntungan Pemasaran Ayam Ras Pedaging (Broiler) di PT. Ciomas Adisatwa Kota Metro - Parel Heldi; Asek A; Herawati M (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2018)
The aim of this research is from this research to find out 1) what kind of marketing institution plays a role in the marketing of broiler chickens in the partnership of PT. Ciomas Adisatwa and 2) price margins, profits, and marketing profits for broiler broiler at PT. Ciomas Adisatwa Metro City. The research method used in the research is using quantitative descriptive method. The research sample is a partnership farmer of PT. Ciomas Adisatwa, traders, and end consumers who buy chicken sourced from partnership farmers. Data analysis techniques used are analysis of price margins, profits, and profit share. The results of the research are three channels of marketing broiler broiler in Metro City, namely the first channel consists of breeders, collectors I, collectors’ II traders, collectors III, retailers and consumers. The second marketing channel is farmers, collectors I, collectors II, retailers, and consumers. The third marketing channel pattern is breeders, collectors, retailers, and consumers. The highest price margin is found in the pattern of the first third marketing channel, namely at the retail level, while the largest profit share is in the second channel pattern, that is, the collecting traders I. Keywords: Broiler, Price, Profit, Share Profit Margins